Early loading after high closed-wedge tibial osteotomyfor the treatment of gonarhrosis - Golovakha, Maksim; Loskutov, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The article deals with the assessment of using an early load on an extremity after high closed-wedge tibial osteotomy for the treatment of arthrosis of the knee joint. Complications were assessed and results of the treatment in two groups of patients were compared; in 34 patients, the extremity was loaded only after the 6th week, and 15 patients were allowed to load their extremity on days 5-7. Apositive effect and a safe use of an early load after closed-wedge osteotomy of the tibia are shown. The use of an early load on the extremity after high closed-wedge osteotomy of the tibia did not result in any worsening of the treatment results. An early load following high closed-wedge osteotomy of the tibia did not increase a share of postoperative complications. The use of an early load after high closed-wedge osteotomy of the tibia made it possible to reduce the terms of the restoration of the operated extremity function.